2021
DOI: 10.1093/milmed/usaa578
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Conventional Outcomes and Immersive Balance Task Performance in Service Members With Mild Traumatic Brain Injury

Abstract: Introduction Mild traumatic brain injury (mTBI) is associated with significant financial cost and reduced military readiness and impacts quality of life for active duty service members (SMs). Post-concussive symptoms can include vestibular impairments, such as chronic dizziness and postural instability, which can be compounded by psychological comorbidities like PTSD. Comprehensive vestibular evaluations are required to assess symptoms and guide clinical decision-making. At the National Intre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…One study [22] leveraged magnetic resonance spectroscopic imaging that is not currently available or conducive for use in operational environments. Similarly, three studies [23][24][25] leveraged the Computer Assisted Rehabilitation Environment (CAREN) system (Motek Medical, Houten, The Netherlands). The size and cost of the CAREN system, in addition to the need for a specialized engineer operator to build scenarios and run the system, make it ill-suited for use in operational environments.…”
Section: Resultsmentioning
confidence: 99%
“…One study [22] leveraged magnetic resonance spectroscopic imaging that is not currently available or conducive for use in operational environments. Similarly, three studies [23][24][25] leveraged the Computer Assisted Rehabilitation Environment (CAREN) system (Motek Medical, Houten, The Netherlands). The size and cost of the CAREN system, in addition to the need for a specialized engineer operator to build scenarios and run the system, make it ill-suited for use in operational environments.…”
Section: Resultsmentioning
confidence: 99%
“…The FGA was developed for patients with vestibular disorders as a modification of the Dynamic Gait Index (DGI) and was designed to reduce the ceiling effect seen on the DGI ( 24 ). Like the BBS, the FGA has since been used for other clinical populations including stroke ( 41 43 ) and mild TBI ( 44 , 45 ). In this study, we found a ceiling effect on both the FGA and BBS which brings into question their utility in this population.…”
Section: Discussionmentioning
confidence: 99%